STUDY OF FOOD ADDITIVES COMPOSITION IN COMMERCIALLY PROCESSED BEEF PRODUCTS - Mirza Rizqi Zulkarnain; Glorya Pricillia; Yasmina Okinurshabani (Jurnal Teknologi dan Industri Pangan, 2021)
Beef is one of the favorite red meats containing various essential nutrients. In the processed beef products, food additives are used for multiple purposes including preservation, moisture and texture re-tention, improvement of flavor and stability of color. The purpose of this study is to identify the food additives composition of halal and local-based commercially processed beef products based on the label of the products and the Indonesian regulations. There were 40 various commercially processed beef pro-ducts assessed in this study. The food additives that were observed were flavor enhancers, preservatives, stabilizers, antioxidants, acidity regulators, and colorants. The types of food additives used in beef sausage products were stabilizers (30.00%), preservatives (25.56%), flavor enhancers (15.56%), colorants (14.44%), antioxidants (13.33%) and acidity regulator (1.11%). In beef balls products there were stabilizers (50.00%), flavor enhancers (20.00%), preservatives (15.00%), antioxidants, acidity regulators and co-lorants (5.00% each). The additives in beef burgers products include stabilizers (29.73%), preservatives (24.32%), colorants (21.62%), flavor enhancers (13.51%), antioxidants and acidity regulators (5.41% each). Corned beef products contain preservatives (32.00%), flavor enhancers and antioxidants (24.00% each), and stabilizers (20.00%). Additionally, smoked beef products use preservatives (50.00%), stabilizers (37.50%) and antioxidants (12.50%). The only food additives used in beef floss products was flavor enhancer (100%). The study suggests that Government Regulations on food additives should be reconsidered. Although the additives are still allowed in Indonesian regulations at the present, food additives of which are included in the list of carcinogenic agents shall be limited or even avoided. Future research to find safer alternatives for those food additives is recommended.